ECOLOGICALLY SAFE PROTECTION OF BLACK CURRANT (RIBES NIGRUM L.) AGAINST SUCKING PESTS - Mostoviak, S. M.; Mostoviak, I. I. (Scientific Progress & Innovations, 2021)
Crop protection chemicals are most commonly used to protect black currant from pests, but there are a number of restrictions on the use of pesticides on berry plantations. The application of biological preparations based on microorganisms and biocidal substances of plants is an alternative to crop protection chemicals. The possibility of reducing the number of sucking insect pests from the family of Tortricidae and Aphidinea on black currant plants (Ribes nigrum L.) under the use of preparations of biological origin based on the complex of natural avermectins – Actoverm, KE and biocidal substances of petunia tincture (Petunia hubrіda Holt.) – was established. Spraying black currant bushes with petunia tincture restrained the infestation of plants by aphids on a par with Aktelik 500 EC chemical insecticide. Biocide compounds of petunia did not have a significant effect on the development and reproduction of Tortricidae, and the colonization of Tortricidae caterpillars was at the level of 1.82.0 pcs/plant. Spraying black currant plants with Aktoverm, KE biological preparation was more effective in controlling the number of pests than the use of petunia tincture, and enabled to reduce the number of Tortricidae by 3.33.5 times in comparison with the control. The technical efficacy of applying petunia tincture against Tortricidae was 4647 %, Actoverm, KE preparation 7071 %, Aktelik 500 EC chemical insecticide 8991 %. The technical effectiveness of all tested preparations against Aphidinea was at the same level and made 6062 %. The positive effect of biological crop protection products from pests on the activity indicators of physiological and biochemical processes in black currant plants was detected. In particular, an increase in the content of chlorophyll and sugars in black currant leaves by 4548 % was registered and it was by 3741 % higher under the use of petunia tincture and by 4853 % and 4449 % under the application of Aktoverm, KE biological preparation. The increase in the content of phenolic compounds under the use of petunia tincture and the bio-preparation was insignificant (910 %). Three-time spraying of black currant plants during the growing season increased the yield of berries by 4450 % as compared with the control and enabled to obtain the yield increase of 2.052.26 t/ha on the average with improved quality indicators (ascorbic acid content  189.6191.3 mg%, sugars 7.487.52 %, and total acidity 1.931.96 %). The application of petunia tincture ensured the yield of berries at the level of 6.166.39 t/ha with a high content of ascorbic acid (at the level of 196 mg%), sugars (7.297.38 %) and the low level of total acidity (1.891.91 %).